Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada Kantor Kecamatan Beji Depok - Asep Purnama (STIKes Ibnu Sina Ajibarang, 2025)
Beji District Office is 1 of 11 districts in the city of Depok which has the task of assisting the Mayor in coordinating the implementation of general government affairs, government affairs in the field of community empowerment and sub-districts as well as the delegation of some government affairs in other fields.The sample in the study was 38 respondents using saturated sampling techniques, all populations in this study were used as research samples. The data collection technique uses a questionnaire method with a Likert scale. Based on the results of this study, the variable Work Environment (X1) has a positive and significant influence on Employee Performance (Y) obtained from the calculation of the calculation of the ttable > (4.217 > 1.690) with a significance level of 0.001 < 0.05. The Work Discipline Variable (X2) has a positive and significant influence on Employee Performance (Y). This is shown from the results of the calculation of the tcount > ttable (5.176 > 1.690) with a significant level of 0.001<0.05. Simultaneously, the variables of Work Environment (X1) and the variables of Employee Performance (X2) have a positive and significant influence on Employee Performance (Y). This was obtained from the results of the calculation of Fcount of 171.585 with a significant level of 0.001 < 0.05 and Fcal > Ftabel (171.585 > 3.27). The results of the analysis of the determination coefficient (R2) obtained R Square of 0.907 or 90.7% were influenced by the variables of Work Environment (X1) and the variable of Work Discipline (X2) while the remaining 9.3% were influenced by other independent variables that were not studied in this study. Keywords: ,,